2011
DOI: 10.1177/1053815111400415
|View full text |Cite
|
Sign up to set email alerts
|

The Need for More Effective Father Involvement in Early Autism Intervention

Abstract: Fathers of children with autism spectrum disorders (ASD) are underrepresented in both early intervention and research. However, fathers have unique interaction styles that make important contributions to the language and symbolic play development of typically developing children. Fathers may make similar contributions to the development of their children with ASD, who struggle with social-communicative deficits, particularly in the areas of language and symbolic play. This article provides a theoretical ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 108 publications
9
102
0
10
Order By: Relevance
“…Results of this study support the findings of previous studies (Dunst et al, 1994;Flippin & Crais, 2011;IDEA Part C, 2004;Sloper, 1999;Stalker, 1990) which proves that the relationship between father involvement with early intervention program is positive and significant in the context of the father involvement in the early intervention program. Father involvement clearly play a large role in influencing the existing early intervention program.…”
Section: Resultssupporting
confidence: 82%
“…Results of this study support the findings of previous studies (Dunst et al, 1994;Flippin & Crais, 2011;IDEA Part C, 2004;Sloper, 1999;Stalker, 1990) which proves that the relationship between father involvement with early intervention program is positive and significant in the context of the father involvement in the early intervention program. Father involvement clearly play a large role in influencing the existing early intervention program.…”
Section: Resultssupporting
confidence: 82%
“…Apesar de já evidenciada a relevância do envolvimento paterno, ainda se nota a falta de intervenções direcionadas para o aprimoramento específico da atuação do pai junto a seu filho (Benzies, Magil-Evans, Hayden, & Ballantyne, 2013;Flippin & Crais, 2011), bem como a fragilidade metodológica desses programas, quando existentes (Bronte-Tinkew, Burkhauser, & Metz, 2012). Embora recentemente algumas intervenções para pais (homens) já tenham sido criadas, estas, no entanto, não contam com robustos procedimentos de avaliação do envolvimento paterno (Bronte-Tinkew et al, 2007;Lundahl, Tollefson, Risser, & Lovejoy, 2008;McAllister, Burgess, Kato, & Barker, 2012).…”
Section: Avaliação Do Envolvimento Paternounclassified
“…The definition of primary caregiver in EI/ECSE has been a critical issue (Flippin & Crais, 2011). The term primary caregiver is a multidimensional and evolving concept, and used interchangeably among EI/ECSE programs and related services.…”
Section: Definition Of Primary Caregivermentioning
confidence: 99%
“…Align with the previous studies, Cheatham and Santos (2011) noted that when parent participation for non-English speaking parents provided through language interpretation services and being careful and respectful, the educational outcomes of children with disabilities are more likely to result positively. Lastly, systematic reviews indicated that EI/ECSE programs by the application of supporting meaningful ad functional parent participation seem most promising to influence child's development (Flippin, & Crais, 2011;Matson, Mahan, & LoVullo, 2009).…”
Section: Child Outcomesmentioning
confidence: 99%
See 1 more Smart Citation